2008
DOI: 10.1080/09548980802244221
|View full text |Cite
|
Sign up to set email alerts
|

An invariance principle for maintaining the operating point of a neuron

Abstract: Sensory neurons adapt to changes in the natural statistics of their environments through processes such as gain control and firing threshold adjustment. It has been argued that neurons early in sensory pathways adapt according to information-theoretic criteria, perhaps maximising their coding efficiency or information rate. Here, we draw a distinction between how a neuron's preferred operating point is determined and how its preferred operating point is maintained through adaptation. We propose that a neuron's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 36 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…but we prefer the equivalent although somewhat more intuitive parametrisation (Elliott et al, 2008) r…”
Section: Plasticitymentioning
confidence: 99%
See 4 more Smart Citations
“…but we prefer the equivalent although somewhat more intuitive parametrisation (Elliott et al, 2008) r…”
Section: Plasticitymentioning
confidence: 99%
“…The parameters Γ and Θ are constants intrinsic to the neuron that determine the neuron's preferred operating point. For more general input statistics, these rules will result in only approximate invariance, but we suggested that real neurons, in the face of intrinsic noise and stochasticity, may not need to maintain precise invariance and that these rules may be good enough for most practical purposes (Elliott et al, 2008).…”
Section: Adapting θ and γ To The Statistics Of A Neuron's Total Inputmentioning
confidence: 99%
See 3 more Smart Citations